The Importance of Developing E-Books Using The 4S-TMD Method to Improve Environmental Literacy - Fitriyanti Sahra, Intan; Sahra, Sjaeful (KnE Social Sciences, 2024)
This preliminary study aimed to describe the importance of developing redox electronic books using the 4S-TMD method to increase environmental literacy. The 4S-TMD method consists of four stages: selection, structuring, characterization and didactic reduction. This study focused on the selection stage as a first step. Environmental literacy is the ability to understand and interpret ecological conditions. From the results of this understanding and interpretation, an individual can decide the appropriate action to maintain, restore and improve the condition of an environment. The components of environmental literacy that must be achieved include ecological knowledge, attitudes towards the environment, cognitive skills, and behavior towards the environment. This study used the Development Research (DR) method with the Design, Development and Evaluation type. This article discussed the importance of developing chemistry e-books in the selection stage. The results of the selection stage determined basic competencies, which are formulated as learning indicators and concept labels based on curriculum demands. The results of the selection stage were also related to the context of content related to everyday life and the development of basic concepts sourced from international textbooks, as well as pedagogic contexts related to achieving environmental literacy. The results of the selection stage were evaluated by expert lecturers in chemistry education who were declared valid. Based on the results and discussion of the research, it was concluded that the development of electronic books on redox material using the 4S TMD method was developed in several stages where the first stage, the selection stage, showed that development began with the selection of basic competencies, namely KD 3.9, by experiencing the development of indicators, namely eight indicators. Keywords: redox, electronic books, 4S-TMD method, environmental literacy